Blood-brain barrier dysfunction and recovery after ischemic stroke. (April 2018) - Jiang, Xiaoyan; Andjelkovic, Anuska V.; Zhu, Ling; Yang, Tuo; Bennett, Michael V.L.; Chen, Jun; Keep, Richard F.; Shi, Yejie
Highlights: Mechanisms of blood-brain barrier dysfunction after ischemic stroke. Regulation of blood-brain barrier integrity by cells in the neurovascular unit. Stroke comorbidities and blood-brain barrier dysfunction. Blood-brain barrier recovery and repair after ischemic stroke. Advanced tools to study the blood-brain barrier. Abstract: The blood-brain barrier (BBB) plays a vital role in regulating the trafficking of fluid, solutes and cells at the blood-brain interface and maintaining the homeostatic microenvironment of the CNS. Under pathological conditions, such as ischemic stroke, the BBB can be disrupted, followed by the extravasation of blood components into the brain and compromise of normal neuronal function. This article reviews recent advances in our knowledge of the mechanisms underlying BBB dysfunction and recovery after ischemic stroke. CNS cells in the neurovascular unit, as well as blood-borne peripheral cells constantly modulate the BBB and influence its breakdown and repair after ischemic stroke. The involvement of stroke risk factors and comorbid conditions further complicate the pathogenesis of neurovascular injury by predisposing the BBB to anatomical and functional changes that can exacerbate BBB dysfunction. Emphasis is also given to the process of long-term structural and functional restoration of the BBB after ischemic injury. With the development of novel research tools, future research on the BBB is likely to reveal promising potential therapeutic targets for protecting the BBB and improving patient outcome after ischemic stroke.